The State of ICT in Uganda - Gillwald, Alison; Mothobi, Onkokame; Ndiwalana, Ali; Tusubira, Tusu (International Development Research Centre IDRC, 2019)
In line with global commitments to improve digital inclusion and to realise the Sustainable Development Goals for 2030, the Government of Uganda has committed the country to developing a digital vision for Uganda. It aims to build a digitally-enabled society that is “… secure, sustainable, innovative, transformative … to create a positive social and economic impact through technology-based empowerment”. The Digital Uganda Vision provides an overarching framework that responds to the national Vision 2040 by providing a unified ICT policy direction. It further provides the Government’s integrated policy and strategic framework to show how information and communication technologies (ICT) can empower Ugandan citizens and achieve the goals of universal inclusion, sustainable development, economic progress and poverty eradication through digital innovation.